A man of many parts : Gissing's short stories, essays and other works - Rawlinson, Barbara (Costerus, 2006)
"This comprehensive study of George Gissing's short stories and related non-fiction is essential reading for students of nineteenth-century realism. For the first time readers will be able to follow the development which transformed Gissing's unremarkable early stories into the very individual tales that elevated his work to the vanguard of realistic short fiction."--Jacket